Implementasi Strategi Digital Marketing Sebagai Inovasi Kreatif di Bidang Wirausaha Nails Art - Satrio, Banu Radyto Dwi; Andini, Raissa Azaria; Sahara, Siti (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Nail treatment has become an important aspect for all groups of women. The use of fake nails Press on nails has become a popular alternative in the beauty industry, especially in nail art. Recently, the press on technique has become a significant trend among nail art fans. This study analyzes the factors that influence the popularity of press on nails and their impact on the development of entrepreneurial business in the nail art industry. The results showed that the popularity of press on nails in the nail art entrepreneur industry is determined by several main factors such as ease of use, application speed, design variations, and endurance. In addition, effective marketing strategies such as the use of social media and collaboration with influencers also play an important role in increasing the popularity of press on nails.